Evaluating the effect of different combination of impression and pouring materials on marginal and internal adaptation of zirconia crowns. - Safoura Ghodsi; Sara Mogharrabi; Samane Jalali; Asadallah Ahmadzadeh; Sara Valizadeh (Universidad de Concepción., 2020)
Purpose: Two important factors in dental prosthesis are making an accurate impression and producing a suitable cast which represents the exact relationship between prepared tooth and oral structures. This study, aimed to investigate the effects of different combinations of impression and pouring materials on marginal and internal adaptation of premolar zirconia crowns. Material and Methods: Forty maxillary premolars were prepared considering round shoulder finish line. The impressions were made either by additional (Panasil) or condensation (Speedex) silicon, and poured by two different types of gypsum materials (Siladent or GC gypsum) (N=10). Zirconia crowns were fabricated using a CAD-CAM system. The crowns were cemented, and the samples were cut in bucco-lingual direction. Marginal and internal gaps were measured by stereomicroscope (×25). Results: The mean marginal gaps for Pansil-Siladent, Panasil-GC, Speedex-Siladent, and Speedex-GC were 141 μm, 143 μm, 131 μm, and 137 μm respectively. The internal gaps were 334 μm, 292 μm, 278 μm, and 257 μm respectively. The independent T-Student test showed no significant differences in average marginal or internal gap among various impression and gypsum materials or their interactions (p>0.05). Two-way ANOVA test showed no significant differences in maximum marginal or internal gap among various impression and gypsum materials and their interactions (p>0.05). Conclusion: The present study revealed no statistically significant difference in marginal/internal gap among crowns prepared using different combinations of impression-pouring materials evaluated.